2006
DOI: 10.3748/wjg.v12.i14.2205
|View full text |Cite
|
Sign up to set email alerts
|

Echo-enhanced ultrasound with pulse inversion imaging: A new imaging modality for the differentiation of cystic pancreatic tumours

Abstract: Cystic pancreatic masses have a different vascularization pattern at echo-enhanced sonography. These characteristics are useful for their differential diagnosis, but histology is still the gold standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…With larger vessels in vicinity blooming artifacts may compromise image quality [22][23][24]. As harmonic imaging technique, CEH-EUS offers better image resolution than power Doppler imaging of suspicious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…With larger vessels in vicinity blooming artifacts may compromise image quality [22][23][24]. As harmonic imaging technique, CEH-EUS offers better image resolution than power Doppler imaging of suspicious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These contrast agents can produce harmonic signals at low acoustic power [20][21][22][23], and are possibly available even for CH-EUS which has limited bandwidths and low acoustic power. Kitano et al showed that CH-EUS with Sono Vue was useful for imaging digestive diseases including pancreaticobiliary malignancies, although the study population was small [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, second generation contrast agents for ultrasonography have been developed and contrast-enhanced harmonic imaging with EUS (CH-EUS) is now possible [18,19]. These agents can produce harmonic signals at low acoustic power [20][21][22][23], and therefore, be available even for EUS imaging [18,19]. Sonazoid, a second generation contrast agent, has been reported to be useful in the diagnosis of hepatocellular carcinoma by highlighting tumor microvasculature [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In einer Kontrastmittelstudie [61] konnte in Übereinstim-mung mit den bisherigen Literaturangaben gezeigt werden, dass eine Iso-oder Hypervaskularisation in der Zystenwand oder in den festen Anteilen der Zysten im Vergleich zum umgebenden Gewebe ein Zeichen für einen zystischen Tumor darstellt, wobei dies jedoch keinen Rückschluss auf die Benignität bzw. Malignität der Läsion erlaubt.…”
Section: Differentialdiagnose Von Zystischen Pankreastumoren Mittels unclassified